25.2k views
5 votes
3x+7y=11
x-y=0
solve by using elimination and substitution method​

User Redwood
by
6.3k points

2 Answers

3 votes

Answer:

x = y = 1,1

Explanation:

x - y = 0 => x = y

3x + 7y = 11 => 3x + 7x = 11 <=> 10x = 11 <=> x = 1,1

=> y = 1,1 (because x = y)

User Ddegasperi
by
6.9k points
7 votes

Answer:

x =
(11)/(10)

y =
(11)/(10)

Explanation:

By elimination method

3x +7y = 11 ......eqn(1)

x - y = 0 .......eqn(2)

Mulitplying equation (2) with 7 we get:

7x - 7y = 0 ..........eqn(3).

Adding equation (1) and (3), we get:

10x = 11

x =
(11)/(10)

Now plugging the value of x in equation (2) we get:

y =
(11)/(10)

By substitution method

x - y = 0

x = y.............eqn(4)

3x + 7y = 11........eqn(5)

Substituting the value of x in equation (5) we get:

y =
(11)/(10)

Now plugging the value of y in equation (3) we get:

x =
(11)/(10).

User Leo Ufimtsev
by
5.9k points